Forecasting human capital of EU member countries accounting for sociocultural determinants. (September 2019) - Marois, Guillaume; Sabourin, Patrick; Bélanger, Alain
Abstract: Inclusion of additional dimensions to population projections can lead to an improvement in the overall quality of the projections and to an enhanced analytical potential of derived projections such as literacy skills and labor force participation. This paper describes the modeling of educational attainment of a microsimulation projection model of the European Union countries. Using ordered logistic regressions on five waves of the European Social Survey, we estimate the impact of mother's education and other sociocultural characteristics on educational attainment and implement them into the microsimulation model. Results of the different projection scenarios are contrasted to understand how the education of the mother and sociocultural variables may affect projection outcomes. We show that a change in the impact of mother's education on children's educational attainment may have a big effect on future trends. Moreover, the proposed approach yields more consistent population projection outputs for specific subpopulations.